Method for predicting bonding performance of high-nitrogen steel / titanium interface

By constructing a composite model of titanium-titanium-based brazing-high nitrogen steel interface and performing atomic replacement, the problem of unstable performance of titanium/high nitrogen steel brazing joints is solved, and production efficiency and performance optimization are improved.

CN119282297AActive Publication Date: 2025-01-10NORTH CHINA UNIV OF WATER RESOURCES & ELECTRIC POWER +2

Patent Information

Application Number
CN202411565515.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-10
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The performance of prior art in titanium/high nitrogen steel brazed joints is unstable, difficult to predict and improve, resulting in low production efficiency.

Method used

By constructing the titanium crystal structure model, the titanium-based brazing crystal structure model and the high-nitrogen steel crystal structure model, the titanium-titanium-based brazing-high-nitrogen steel interface composite model was constructed, atomic replacement and multi-dimensional performance evaluation were performed, and the target titanium-based was determined. The solder is used to optimize interface bonding performance.

Benefits of technology

Improve the performance and production efficiency of titanium/high nitrogen steel brazed joints, ensuring the stability and performance optimization of brazed joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119282297A_ABST
    Figure CN119282297A_ABST
Patent Text Reader

Abstract

The invention provides a method for predicting the bonding performance of a high-nitrogen steel / titanium interface, and the method comprises the steps: constructing a titanium crystal structure model, a titanium-based brazing filler metal crystal structure model corresponding to titanium-based brazing filler metal, and a high-nitrogen steel crystal structure model, constructing a titanium-titanium-based brazing filler metal-high-nitrogen steel interface composite model on the basis of a titanium crystal structure model according to a titanium crystal cell crystal face obtained through segmentation in a corresponding first segmentation mode, and carrying out atom replacement on atoms of the titanium-titanium-based brazing filler metal-high-nitrogen steel interface composite model for multiple times to obtain the titanium-titanium-based brazing filler metal-high-nitrogen steel interface composite model. The titanium-titanium-based brazing filler metal-high-nitrogen steel interface composite models are subjected to atom replacement, multiple different titanium-titanium-based brazing filler metal-high-nitrogen steel interface composite models obtained after atom replacement are obtained, the titanium-titanium-based brazing filler metal-high-nitrogen steel interface composite models obtained before and after atom replacement are subjected to multi-dimensional bonding performance evaluation, and multi-dimensional bonding performance parameter indexes are obtained; and a target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model meeting the target requirement is determined, and the titanium-based brazing filler metal corresponding to the target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model is determined as the target titanium-based brazing filler metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of dissimilar material connection, and in particular to a method for predicting high nitrogen steel / titanium interface bonding performance. Background Art

[0002] Since the brazing connection of dissimilar materials can reduce material costs and improve the flexibility of structural materials, it has attracted more and more attention from the industry. Among them, high nitrogen austenitic stainless steel (referred to as high nitrogen steel) is mainly used in aviation, medical and other fields. High nitrogen steel has the advantages of good toughness and corrosion resistance, while metal titanium has the advantages of high strength, good rigidity, excellent high temperature mechanical properties, excellent biocompatibility, etc. It is widely used in aerospace, new energy and biomedical fields, and is an ideal high temperature structural material. However, the production cost of titanium and its alloys is high, the material utilization rate is low, and the production process is complex, which limits the wide application of titanium and its alloys in industrial production and medical fields. At the same time, the brazing connection of dissimilar materials of titanium and high nitrogen steel can make the composite structural parts give full play to their advantages in performance, while reducing the complexity of the workpiece structure and reducing costs. Therefore, the brazing connection of titanium / high nitrogen steel materials has broad application prospects in the fields of aerospace, petrochemical and medical equipment. However, due to the great differences in physical and chemical properties between titanium and high nitrogen steel, specifically in terms of melting point, thermal expansion coefficient, thermal conductivity, etc., the requirements for brazing heat input are relatively harsh, and brittle Ti-Fe intermetallic compounds are easily formed.

[0003] At present, the connection of titanium / high nitrogen steel is mainly achieved by adjusting brazing process parameters, adding intermediate layers, etc., and traditional characterization and analysis methods are used to study the joint structure and bonding properties.

[0004] However, the performance of the titanium / high nitrogen steel brazed joint prepared by the current method of brazing first and then analyzing is not stable. It is also difficult to predict the bonding performance of the titanium / high nitrogen steel brazed joint to improve the performance of the titanium / high nitrogen steel brazed joint, resulting in low production efficiency of the titanium / high nitrogen steel brazed joint. Summary of the invention

[0005] In view of this, the purpose of the present application is to provide a method for predicting the bonding performance of a high nitrogen steel / titanium interface, by constructing a titanium crystal structure model, a titanium-based brazing filler metal crystal structure model and a high nitrogen steel crystal structure model to construct a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, by performing atomic replacement on the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model multiple times to obtain a variety of different titanium-titanium-based brazing filler metal-high nitrogen steel interface composite models after atomic replacement, and performing a multi-dimensional bonding performance evaluation on the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model before and after atomic replacement, determining a target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, and determining the titanium-based brazing filler metal corresponding to the target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model as a target titanium-based brazing filler metal, so as to predict the influence of different titanium-based brazing fillers on the bonding performance of the titanium / high nitrogen steel interface, so as to determine the target titanium-based brazing filler metal with the best bonding performance, and using the target titanium-based brazing filler metal can ensure the performance of the titanium / high nitrogen steel brazing joint, thereby improving the production efficiency of the titanium / high nitrogen steel brazing joint.

[0006] In a first aspect, an embodiment of the present application provides a method for predicting high nitrogen steel / titanium interface bonding performance, the method comprising:

[0007] Constructing a titanium crystal structure model, a titanium-based solder crystal structure model corresponding to the titanium-based solder, and a high-nitrogen steel crystal structure model; wherein the Ti atoms, Fe atoms, and Zr atoms in the titanium-based solder crystal structure model correspond to the Ti element, Fe element, and Zr element in the titanium-based solder; and the proportions of the Ti element, Fe element, and Zr element in titanium-based solders of different components are different;

[0008] Based on the titanium crystal structure model obtained by cutting the titanium unit cell crystal plane according to the corresponding first cutting method, a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model is constructed;

[0009] By repeatedly performing atomic replacement on the atoms of the titanium-titanium-based solder-high nitrogen steel interface composite model, a plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after the atomic replacement are obtained; wherein the titanium-titanium-based solder-high nitrogen steel interface composite model before the atomic replacement and the plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after the atomic replacement correspond to titanium-based solders of different components, respectively;

[0010] The multi-dimensional bonding performance evaluation was conducted on the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement to obtain multi-dimensional bonding performance parameter indicators;

[0011] From the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement, determine the target titanium-titanium-based solder-high nitrogen steel interface composite model whose multi-dimensional combined performance parameter indicators meet the target requirements, and determine the titanium-based solder corresponding to the target titanium-titanium-based solder-high nitrogen steel interface composite model as the target titanium-based solder.

[0012] In a possible implementation, the titanium unit cell crystal plane obtained by cutting the titanium crystal structure model according to the corresponding first cutting method is used to construct a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, including:

[0013] Determine a first cutting method corresponding to the titanium crystal structure model, a second cutting method corresponding to the titanium-based solder crystal structure model, and a third cutting method corresponding to the high-nitrogen steel crystal structure model, and cut the corresponding crystal structure models based on different cutting methods to obtain a plurality of crystal structure models after cutting; wherein the titanium unit cell crystal structure model after cutting includes a plurality of titanium unit cell crystal planes; the titanium-based solder crystal structure model after cutting includes a plurality of titanium-based solder crystal planes; the high-nitrogen steel crystal structure model after cutting includes a plurality of high-nitrogen steel crystal planes;

[0014] The titanium-titanium-based brazing filler material-high nitrogen steel interface composite model is constructed based on target titanium unit cell crystal planes that meet the crystal plane screening conditions among multiple titanium unit cell crystal planes, target titanium-based brazing filler material crystal planes that meet the crystal plane screening conditions among multiple titanium-based brazing filler material crystal planes, and target high nitrogen steel crystal planes that meet the crystal plane screening conditions among multiple high nitrogen steel crystal planes.

[0015] In a possible implementation, each crystal plane includes multiple atomic layers; the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model is constructed based on a target titanium unit cell crystal plane that meets the crystal plane screening conditions among multiple titanium unit cell crystal planes, a target titanium-based brazing filler metal crystal plane that meets the crystal plane screening conditions among multiple titanium-based brazing filler metal crystal planes, and a target high nitrogen steel crystal plane that meets the crystal plane screening conditions among multiple high nitrogen steel crystal planes, including:

[0016] Conducting convergence tests on the atomic layers in the plurality of titanium unit cell crystal planes, the plurality of titanium-based brazing filler metal crystal planes, and the plurality of high nitrogen steel crystal planes, respectively, to obtain convergence test results corresponding to each crystal plane;

[0017] According to the convergence test results corresponding to each crystal plane, a target titanium unit cell crystal plane that meets the convergence requirements among multiple titanium unit cell crystal planes, a target titanium-based solder crystal plane that meets the convergence requirements among multiple titanium-based solder crystal planes, and a target high-nitrogen steel crystal plane that meets the convergence requirements among multiple high-nitrogen steel crystal planes are respectively screened out;

[0018] The titanium-titanium-based solder-high nitrogen steel interface composite model is constructed based on the target titanium unit cell crystal plane, the target titanium-based solder crystal plane and the target high nitrogen steel crystal plane.

[0019] In a possible implementation, after constructing the titanium crystal structure model, the titanium-based brazing filler metal crystal structure model corresponding to the titanium-based brazing filler metal, and the high nitrogen steel crystal structure model, the method for predicting the high nitrogen steel / titanium interface bonding performance further includes:

[0020] The corresponding first optimization parameters are determined based on the titanium, the titanium-based brazing filler metal and the high nitrogen steel; wherein the first optimization parameters include the k grid points for summing the Brillouin zones, the plane wave cutoff energy, the convergence standard of the system energy, the internal stress and the displacement; wherein the k grid points are 4×4×1 k grid points, the plane wave cutoff energy is 381eV, the convergence standard of the system energy is 1×10-5eV / atom, the internal stress is less than 0.05GPa, and the displacement is less than

[0021] Based on the first optimization parameter, the titanium crystal structure model, the titanium-based brazing filler metal crystal structure model and the high nitrogen steel crystal structure model are structurally optimized to obtain the titanium crystal structure model, the titanium-based brazing filler metal crystal structure model and the high nitrogen steel crystal structure model after structural optimization.

[0022] In a possible implementation, after constructing the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, the method for predicting the high nitrogen steel / titanium interface bonding performance further includes:

[0023] The corresponding second optimization parameters are obtained based on the titanium, the titanium-based brazing filler metal and the high nitrogen steel; wherein the second optimization parameters include the k grid points for summing the Brillouin zone, the plane wave cutoff energy, the convergence standard of the system energy, the internal stress and the displacement; the k grid points are 3×3×1, the plane wave cutoff energy Ecut is 326.5 eV, and the convergence standard of the system energy is 2×10 -5 eV / atom, the internal stress is less than 0.1GPa, and the displacement is less than

[0024] The titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model is structurally optimized based on the second optimization parameter to obtain the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model after structural optimization.

[0025] In a possible implementation, the multi-dimensional bonding performance parameter index includes interface adhesion work, differential charge density diagram, electron localization function diagram, Mulliken layout analysis table, and the multi-dimensional bonding performance evaluation is performed on the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement to obtain a multi-dimensional bonding performance parameter index, including:

[0026] Calculating the interface adhesion work of the titanium-titanium-based solder-high nitrogen steel interface composite model before the atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after the atomic replacement based on a preset interface adhesion work calculation formula;

[0027] Based on the interface adhesion work of the titanium-titanium-based solder-high nitrogen steel interface composite model before the atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after the atomic replacement, the corresponding bonding performance parameter index is obtained.

[0028] In a possible implementation manner, the interfacial adhesion work is calculated by the following calculation formula:

[0029] W ad =(E A +E B +E C -E A / B / C ) / 2A

[0030] Among them, W ad is the interfacial adhesion work; E A 、E B 、E C E is the total energy of the crystal structure model of the titanium metal surface, titanium-based brazing filler metal, and high nitrogen steel surface; A / B / C is the energy of the interface composite model; A is the cross-sectional area of ​​the interface composite model.

[0031] In a possible implementation, the multi-dimensional bonding performance evaluation of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement is performed to obtain a multi-dimensional bonding performance parameter index, further comprising:

[0032] Obtaining a first local electron function diagram, a first Mulliken layout analysis table, and a first differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model before the atomic replacement, and a second local electron function diagram, a second Mulliken layout analysis table, and a second differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model after the atomic replacement;

[0033] Based on the first localized electron function diagram, the first Mulliken layout analysis table, the first differential charge density diagram and the second localized electron function diagram, the second Mulliken layout analysis table and the second differential charge density diagram, a multi-dimensional combination performance parameter index is obtained.

[0034] In a second aspect, the present application also provides a device for predicting high nitrogen steel / titanium interface bonding performance, the device comprising:

[0035] The first construction module is used to construct a titanium crystal structure model, a titanium-based solder crystal structure model corresponding to the titanium-based solder, and a high-nitrogen steel crystal structure model; wherein the Ti atoms, Fe atoms, and Zr atoms in the titanium-based solder crystal structure model correspond to the Ti element, Fe element, and Zr element in the titanium-based solder; and the proportions of the Ti element, Fe element, and Zr element in titanium-based solders of different components are different;

[0036] A second construction module is used to construct a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model based on the titanium unit cell crystal plane obtained by cutting the titanium crystal structure model according to the corresponding first cutting method;

[0037] A replacement module is used to obtain a plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement by performing atomic replacement on the atoms of the titanium-titanium-based solder-high nitrogen steel interface composite model for multiple times; wherein the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement correspond to titanium-based solders of different components, respectively;

[0038] An evaluation module is used to perform multi-dimensional bonding performance evaluation on the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement to obtain multi-dimensional bonding performance parameter indicators;

[0039] A determination module is used to determine a target titanium-titanium-based solder-high nitrogen steel interface composite model whose multi-dimensional combined performance parameter indicators meet the target requirements from the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement, and determine the titanium-based solder corresponding to the target titanium-titanium-based solder-high nitrogen steel interface composite model as the target titanium-based solder.

[0040] In a possible implementation manner, the second building module is specifically used to:

[0041] Determine a first cutting method corresponding to the titanium crystal structure model, a second cutting method corresponding to the titanium-based solder crystal structure model, and a third cutting method corresponding to the high-nitrogen steel crystal structure model, and cut the corresponding crystal structure models based on different cutting methods to obtain a plurality of crystal structure models after cutting; wherein the titanium unit cell crystal structure model after cutting includes a plurality of titanium unit cell crystal planes; the titanium-based solder crystal structure model after cutting includes a plurality of titanium-based solder crystal planes; the high-nitrogen steel crystal structure model after cutting includes a plurality of high-nitrogen steel crystal planes;

[0042] The titanium-titanium-based brazing filler material-high nitrogen steel interface composite model is constructed based on target titanium unit cell crystal planes that meet the crystal plane screening conditions among multiple titanium unit cell crystal planes, target titanium-based brazing filler material crystal planes that meet the crystal plane screening conditions among multiple titanium-based brazing filler material crystal planes, and target high nitrogen steel crystal planes that meet the crystal plane screening conditions among multiple high nitrogen steel crystal planes.

[0043] In a possible implementation manner, each crystal plane includes a plurality of atomic layers; and the second building block is specifically configured to:

[0044] Conducting convergence tests on the atomic layers in the plurality of titanium unit cell crystal planes, the plurality of titanium-based brazing filler metal crystal planes, and the plurality of high nitrogen steel crystal planes, respectively, to obtain convergence test results corresponding to each crystal plane;

[0045] According to the convergence test results corresponding to each crystal plane, a target titanium unit cell crystal plane that meets the convergence requirements among multiple titanium unit cell crystal planes, a target titanium-based solder crystal plane that meets the convergence requirements among multiple titanium-based solder crystal planes, and a target high-nitrogen steel crystal plane that meets the convergence requirements among multiple high-nitrogen steel crystal planes are respectively screened out;

[0046] The titanium-titanium-based solder-high nitrogen steel interface composite model is constructed based on the target titanium unit cell crystal plane, the target titanium-based solder crystal plane and the target high nitrogen steel crystal plane.

[0047] In a possible implementation manner, the device for predicting high nitrogen steel / titanium interface bonding properties further includes:

[0048] The first determination module is used to determine the corresponding first optimization parameters based on the titanium, the titanium-based solder and the high-nitrogen steel after constructing the titanium crystal structure model, the titanium-based solder crystal structure model corresponding to the titanium-based solder and the high-nitrogen steel crystal structure model; wherein the first optimization parameters include the k grid points for summing the Brillouin zones, the plane wave cutoff energy, the convergence standard of the system energy, the internal stress and the displacement; wherein the k grid points are 4×4×1 k grid points, the plane wave cutoff energy is 381eV, the convergence standard of the system energy is 1×10-5eV / atom, the internal stress is less than 0.05GPa, and the displacement is less than

[0049] The first optimization module is used to perform structural optimization on the titanium crystal structure model, the titanium-based brazing filler metal crystal structure model and the high nitrogen steel crystal structure model based on the first optimization parameters to obtain the titanium crystal structure model, the titanium-based brazing filler metal crystal structure model and the high nitrogen steel crystal structure model after structural optimization.

[0050] In a possible implementation manner, the device for predicting high nitrogen steel / titanium interface bonding properties further includes:

[0051] The second determination module is used to obtain corresponding second optimization parameters based on the titanium, the titanium-based solder and the high nitrogen steel after constructing the titanium-titanium-based solder-high nitrogen steel interface composite model; wherein the second optimization parameters include k grid points for summing the Brillouin zone, plane wave cutoff energy, convergence standard of system energy, internal stress and displacement; the k grid points are 3×3×1, the plane wave cutoff energy Ecut is 326.5 eV, and the convergence standard of the system energy is 2×10 -5 eV / atom, the internal stress is less than 0.1GPa, and the displacement is less than

[0052] The second optimization module is used to perform structural optimization on the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model based on the second optimization parameters to obtain the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model after structural optimization.

[0053] In a possible implementation, the multi-dimensional bonding performance parameter index includes interface adhesion work, differential charge density map, electron localization function map, Mulliken layout analysis table, and the evaluation module is specifically used for:

[0054] Calculating the interface adhesion work of the titanium-titanium-based solder-high nitrogen steel interface composite model before the atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after the atomic replacement based on a preset interface adhesion work calculation formula;

[0055] Based on the interface adhesion work of the titanium-titanium-based solder-high nitrogen steel interface composite model before the atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after the atomic replacement, the corresponding bonding performance parameter index is obtained.

[0056] In a possible implementation manner, the interfacial adhesion work is calculated by the following calculation formula:

[0057] W ad =(E A +E B +E C -E A / B / C ) / 2A

[0058] Among them, W ad is the interfacial adhesion work; E A 、E B 、E C E is the total energy of the crystal structure model of the titanium metal surface, titanium-based brazing filler metal, and high nitrogen steel surface; A / B / C is the energy of the interface composite model; A is the cross-sectional area of ​​the interface composite model.

[0059] In a possible implementation manner, the evaluation module is further specifically used for:

[0060] Obtaining a first local electron function diagram, a first Mulliken layout analysis table, and a first differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model before the atomic replacement, and a second local electron function diagram, a second Mulliken layout analysis table, and a second differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model after the atomic replacement;

[0061] Based on the first localized electron function diagram, the first Mulliken layout analysis table, the first differential charge density diagram and the second localized electron function diagram, the second Mulliken layout analysis table and the second differential charge density diagram, a multi-dimensional combination performance parameter index is obtained.

[0062] In a third aspect, an embodiment of the present application provides an electronic device, comprising: a processor, a storage medium and a bus, wherein the storage medium stores machine-readable instructions executable by the processor, and when the electronic device is running, the processor communicates with the storage medium through the bus, and the processor executes the machine-readable instructions to perform the steps of the method for predicting the high nitrogen steel / titanium interface bonding performance as described in any one of the first aspects.

[0063] The present application provides a method for predicting the high nitrogen steel / titanium interface bonding performance, which comprises constructing a titanium crystal structure model, a titanium-based solder crystal structure model corresponding to the titanium-based solder, and a high nitrogen steel crystal structure model, constructing a titanium-titanium-based solder-high nitrogen steel interface composite model based on the titanium crystal structure model obtained by cutting the titanium unit cell crystal plane according to the corresponding first cutting method, and performing atomic replacement on the atoms of the titanium-titanium-based solder-high nitrogen steel interface composite model multiple times to obtain a plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement, and performing atomic replacement on the titanium-titanium-based solder-high nitrogen steel interface composite model multiple times to obtain a plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement, and performing atomic replacement on the titanium-titanium-based solder-high nitrogen steel interface composite models multiple times to obtain a plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models multiple times. A multi-dimensional bonding performance evaluation was performed on the solder-high nitrogen steel interface composite model and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement to obtain multi-dimensional bonding performance parameter indicators. From the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement, the target titanium-titanium-based solder-high nitrogen steel interface composite model whose multi-dimensional bonding performance parameter indicators met the target requirements was determined, and the titanium-based solder corresponding to the target titanium-titanium-based solder-high nitrogen steel interface composite model was determined as the target titanium-based solder. In the present application, a titanium crystal structure model, a titanium-based solder crystal structure model and a high-nitrogen steel crystal structure model are constructed to construct a titanium-titanium-based solder-high-nitrogen steel interface composite model, and multiple different titanium-titanium-based solder-high-nitrogen steel interface composite models after atomic replacement are obtained by multiple atomic replacements on the titanium-titanium-based solder-high-nitrogen steel interface composite model. A multi-dimensional bonding performance evaluation is performed on the titanium-titanium-based solder-high-nitrogen steel interface composite model before and after the atomic replacement, and a target titanium-titanium-based solder-high-nitrogen steel interface composite model is determined. The titanium-based solder corresponding to the target titanium-titanium-based solder-high-nitrogen steel interface composite model is determined as the target titanium-based solder. The influence of different titanium-based solders on the bonding performance of the titanium / high-nitrogen steel interface can be predicted to determine the target titanium-based solder with the best bonding performance. The use of the target titanium-based solder can ensure the performance of the titanium / high-nitrogen steel brazing joint, thereby improving the production efficiency of the titanium / high-nitrogen steel brazing joint.

[0064] In order to make the above-mentioned objects, features and advantages of the present application more obvious and easy to understand, preferred embodiments are specifically cited below and described in detail with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0066] Figure 1 is a flow chart of a method for predicting high nitrogen steel / titanium interface bonding performance provided in an embodiment of the present application;

[0067] Figure 2 It is a schematic diagram of the titanium crystal structure model, the high nitrogen steel crystal structure model and the titanium-based solder crystal structure model;

[0068] Figure 3 It is a schematic diagram of a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model before atomic replacement and a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model after atomic replacement;

[0069] Figure 4 It is a schematic diagram of a titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and another titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement;

[0070] Figure 5 is a flow chart of a method for predicting high nitrogen steel / titanium interface bonding performance provided according to another embodiment of the present application;

[0071] Figure 6 is a flow chart of a method for predicting high nitrogen steel / titanium interface bonding performance provided according to another embodiment of the present application;

[0072] Figure 7 is a flow chart of a method for predicting high nitrogen steel / titanium interface bonding performance provided according to another embodiment of the present application;

[0073] Figure 8 is a flow chart of a method for predicting high nitrogen steel / titanium interface bonding performance provided according to another embodiment of the present application;

[0074] Fig. 9 is a flow chart of a method for predicting high nitrogen steel / titanium interface bonding performance provided according to another embodiment of the present application;

[0075] Fig.10 is a schematic diagram of a first differential charge density map and a second differential charge density map;

[0076] Fig.11 is a schematic diagram of a first localized electron function diagram and a second localized electron function diagram;

[0077] Fig.12 It is a schematic diagram of the structure of a device for predicting high nitrogen steel / titanium interface bonding performance provided in an embodiment of the present application;

[0078] Fig.13 It is a structural schematic diagram of an electronic device provided according to an embodiment of the present application. DETAILED DESCRIPTION

[0079] To make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. It should be understood that the drawings in the present application only serve the purpose of explanation and description and are not used to limit the scope of protection of the present application. In addition, it should be understood that the schematic drawings are not drawn in real proportion. The flowchart used in this application shows the operations implemented according to some embodiments of the present application. It should be understood that the operations of the flowchart can be implemented out of sequence, and the steps without logical context can be reversed in order or implemented simultaneously. In addition, those skilled in the art can add one or more other operations to the flowchart under the guidance of the content of the present application, or remove one or more operations from the flowchart.

[0080] In addition, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various configurations. Therefore, the following detailed description of the embodiments of the present application provided in the drawings is not intended to limit the scope of the application claimed for protection, but merely represents the selected embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application.

[0081] It should be noted that the term "comprising" will be used in the embodiments of the present application to indicate the existence of the features declared thereafter, but does not exclude the addition of other features.

[0082] Considering that the brazing connection of dissimilar materials can reduce material costs and improve the flexibility of structural materials, it has attracted more and more attention from the industry. Among them, high nitrogen austenitic stainless steel (referred to as high nitrogen steel) is mainly used in aviation, medical and other fields. High nitrogen steel has the advantages of good toughness and corrosion resistance, while metal titanium has the advantages of high strength, good rigidity, excellent high temperature mechanical properties, excellent biocompatibility, etc. It is widely used in aerospace, new energy and biomedical fields, and is an ideal high temperature structural material. However, the production cost of titanium and its alloys is high, the material utilization rate is low, and the production process is complex, which limits the wide application of titanium and its alloys in industrial production and medical fields. At the same time, the brazing connection of dissimilar materials of titanium and high nitrogen steel can make the composite structural parts give full play to their advantages in performance, while reducing the complexity of the workpiece structure and reducing costs. Therefore, the brazing connection of titanium / high nitrogen steel materials has broad application prospects in the fields of aerospace, petrochemical and medical equipment. However, due to the great differences in physical and chemical properties between titanium and high nitrogen steel, specifically in terms of melting point, thermal expansion coefficient, thermal conductivity, etc., the requirements for brazing heat input are relatively harsh, and brittle Ti-Fe intermetallic compounds are easily formed.

[0083] At present, the connection of titanium / high nitrogen steel is mainly achieved by adjusting brazing process parameters, adding intermediate layers, etc., and the traditional characterization and analysis methods are used to study the joint structure and bonding performance. However, the performance of the titanium / high nitrogen steel brazed joint prepared by the current method of brazing first and then analyzing is not stable, and it is also difficult to predict the bonding performance of the titanium / high nitrogen steel brazed joint to improve the performance of the titanium / high nitrogen steel brazed joint, resulting in low production efficiency of the titanium / high nitrogen steel brazed joint.

[0084] To address this problem, the present application provides a method for predicting the bonding performance of a high nitrogen steel / titanium interface, by constructing a titanium crystal structure model, a titanium-based brazing filler metal crystal structure model, and a high nitrogen steel crystal structure model to construct a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, by performing atomic replacement on the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model multiple times to obtain a plurality of different titanium-titanium-based brazing filler metal-high nitrogen steel interface composite models after atomic replacement, and performing a multi-dimensional bonding performance evaluation on the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite models before and after atomic replacement to determine a target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, and determining the titanium-based brazing filler metal corresponding to the target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model as the target titanium-based brazing filler metal, and the influence of different titanium-based brazing filler metals on the bonding performance of the titanium / high nitrogen steel interface can be predicted to determine the target titanium-based brazing filler metal with the best bonding performance, and the use of the target titanium-based brazing filler metal can ensure the performance of the titanium / high nitrogen steel brazing joint, thereby improving the production efficiency of the titanium / high nitrogen steel brazing joint.

[0085] Figure 1 is a flow chart of a method for predicting high nitrogen steel / titanium interface bonding performance according to an embodiment of the present application, such as Figure 1 As shown, the method for predicting the high nitrogen steel / titanium interface bonding performance in the embodiment of the present application may specifically include the following steps:

[0086] S101, constructing a titanium crystal structure model, a titanium-based brazing filler metal crystal structure model corresponding to the titanium-based brazing filler metal, and a high nitrogen steel crystal structure model.

[0087] In the embodiment of the present application, the titanium crystal structure model, the titanium-based brazing filler metal crystal structure model corresponding to the titanium-based brazing filler metal, and the high nitrogen steel crystal structure model are constructed for subsequent processing. For example, the titanium crystal structure model, the high nitrogen steel crystal structure model, and the titanium-based brazing filler metal crystal structure model are respectively as follows: Figure 2As shown in the left, middle and right parts. Among them, the Ti atoms, Fe atoms, Zr atoms in the titanium-based solder crystal structure model correspond to the Ti element, Fe element, and Zr element in the titanium-based solder, and the proportions of the Ti element, Fe element, and Zr element in the titanium-based solder of different components are different. It can be understood that the titanium-based solder crystal structure models constructed corresponding to different titanium-based solders are also different. Among them, the titanium-based solder can have the following composition in atomic percentage: 75% Ti, 16.67% Fe, 8.33% Zr. This application is described as an example, but it does not constitute a limitation on the titanium-based solder, and it can be set specifically according to actual conditions. It can be seen that the titanium-based solder includes Ti atoms, Fe atoms, and Zr atoms.

[0088] Optionally, a crystal model building tool Visualizer may be used to respectively build a titanium crystal structure model of the metal titanium surface, a titanium-based brazing filler metal crystal structure model of the high nitrogen steel surface, and a high nitrogen steel crystal structure model.

[0089] It should be noted that the construction of the titanium-based solder crystal structure model is based on the titanium unit cell and virtual crystal approximation (VCA). Specifically, the titanium unit cell is obtained, and the titanium-based solder crystal structure model is constructed based on the titanium unit cell and virtual crystal approximation. I will not go into details about this.

[0090] S102, constructing a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model based on the titanium unit cell crystal plane obtained by cutting the titanium crystal structure model according to the corresponding first cutting method.

[0091] In the embodiment of the present application, the cutting method is a method for cutting the crystal structure model, the first cutting method is a method for cutting the titanium crystal structure model, the titanium unit cell crystal plane is a crystal plane obtained by cutting the titanium crystal structure model according to the first cutting method, and based on the titanium unit cell crystal plane obtained by cutting the titanium crystal structure model according to the corresponding first cutting method, a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model is constructed. For example, the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model is as follows: Figure 3 Shown on the left.

[0092] S103, performing atomic replacement on the atoms of the titanium-titanium-based solder-high nitrogen steel interface composite model multiple times to obtain a plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement.

[0093] In the embodiment of the present application, the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the various titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement respectively correspond to titanium-based solders of different components, that is, to different titanium-based solders. The atoms in the titanium-titanium-based solder-high nitrogen steel interface composite model constructed in step S102 are atomically replaced multiple times to obtain various titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement. For example, a titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement is as follows: Figure 3 As shown on the right, comparative solder 1 represents a titanium-based solder with different compositions.

[0094] It should be noted that the present application does not impose too many restrictions on the specific method of repeatedly replacing atoms in the titanium-titanium-based solder-high nitrogen steel interface composite model to obtain a variety of different titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement, and can be set according to actual conditions.

[0095] As a possible implementation method, Fe atoms are used to atomically replace Zr atoms in the titanium-based solder in the titanium-titanium-based solder-high nitrogen steel interface composite model to obtain the titanium-based solder after atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement. Among them, Fe atoms are used to atomically replace Zr atoms in the titanium-based solder in the titanium-titanium-based solder-high nitrogen steel interface composite model to obtain the titanium-titanium-based solder after atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model corresponding to the replaced titanium-titanium-based solder, for example, Figure 3 The comparative solder 1 shown on the right side of the figure represents a replaced titanium-based solder of the present invention. The comparative solder 1 has the following solder composition in terms of atomic percentage: 75% Ti, 25% Fe. At this time, the titanium-titanium-based solder-high nitrogen steel interface composite model corresponding to the replaced titanium-based solder (comparative solder 1) is as follows: Figure 3 The titanium / comparison brazing filler 1 / high nitrogen steel interface composite model is shown on the right.

[0096] As a possible implementation method, Zr atoms are used to atomically replace Fe atoms in the titanium-based solder in the titanium-titanium-based solder-high nitrogen steel interface composite model to obtain the titanium-based solder after atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement. Among them, Zr atoms are used to in-situ replace Fe atoms in the titanium-based solder in the titanium-titanium-based solder-high nitrogen steel interface composite model to obtain the titanium-titanium-based solder after atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model corresponding to the replaced titanium-titanium-based solder, for example, Figure 4The comparative solder 2 shown on the right side of the figure represents a replaced titanium-based solder of the present application. The comparative solder 2 has the following solder composition in terms of atomic percentage: 75% Ti, 25% Zr. At this time, the titanium-titanium-based solder-high nitrogen steel interface composite model corresponding to the replaced titanium-based solder (comparative solder 2) is as follows: Figure 4 The titanium / comparison brazing filler 2 / high nitrogen steel interface composite model is shown on the right.

[0097] S104, performing a multi-dimensional bonding performance evaluation on the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement to obtain a multi-dimensional bonding performance parameter index.

[0098] In the embodiment of the present application, the multi-dimensional bonding performance parameter indicators include interface adhesion work, differential charge density diagram, electron localization function diagram, and Mulliken layout analysis table. The differential charge density diagram is a differential charge density diagram of different atoms under the same functional conditions. The titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement constructed in step S102 and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement obtained in step S103 are subjected to multi-dimensional bonding performance evaluation to obtain multi-dimensional bonding performance parameter indicators for subsequent processing.

[0099] S105, determining a target titanium-titanium-based solder-high nitrogen steel interface composite model whose multi-dimensional combined performance parameter indicators meet the target requirements from the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement, and determining the titanium-based solder corresponding to the target titanium-titanium-based solder-high nitrogen steel interface composite model as the target titanium-based solder.

[0100] In the embodiment of the present application, the target requirement is the preset requirement for the multi-dimensional combination performance parameter index. From the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model before atomic replacement constructed in step S102 and the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model after atomic replacement obtained in step S103, the target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model whose multi-dimensional combination performance parameter index meets the target requirement obtained in step S104 is determined. The titanium-based brazing filler metal corresponding to the target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model is determined as the target titanium-based brazing filler metal, so that the high nitrogen steel / titanium brazing joint can be prepared according to the target titanium-based brazing filler metal subsequently.

[0101] The method for predicting the high nitrogen steel / titanium interface bonding performance provided in the embodiment of the present application constructs a titanium crystal structure model, a titanium-based solder crystal structure model corresponding to the titanium-based solder, and a high nitrogen steel crystal structure model, and constructs a titanium-titanium-based solder-high nitrogen steel interface composite model based on the titanium crystal structure model. The atoms of the titanium-titanium-based solder-high nitrogen steel interface composite model are atomically replaced multiple times to obtain a plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement, and the titanium-titanium-based solder-high nitrogen steel interface composite models before atomic replacement are obtained. The titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement are used for multi-dimensional bonding performance evaluation to obtain multi-dimensional bonding performance parameter indicators, and the target titanium-titanium-based solder-high nitrogen steel interface composite model whose multi-dimensional bonding performance parameter indicators meet the target requirements is determined from the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement, and the titanium-based solder corresponding to the target titanium-titanium-based solder-high nitrogen steel interface composite model is determined as the target titanium-based solder. The method for predicting the high nitrogen steel / titanium interface bonding performance of the present application constructs a titanium crystal structure model, a titanium-based brazing filler metal crystal structure model and a high nitrogen steel crystal structure model to construct a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, performs atomic replacement on the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model multiple times to obtain multiple different titanium-titanium-based brazing filler metal-high nitrogen steel interface composite models after atomic replacement, performs multi-dimensional bonding performance evaluation on the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite models before and after atomic replacement, determines a target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, and determines the titanium-based brazing filler metal corresponding to the target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model as the target titanium-based brazing filler metal. The influence of different titanium-based brazing fillers on the bonding performance of the titanium / high nitrogen steel interface can be predicted to determine the target titanium-based brazing filler metal with the best bonding performance. The use of the target titanium-based brazing filler metal can ensure the performance of the titanium / high nitrogen steel brazing joint, thereby improving the production efficiency of the titanium / high nitrogen steel brazing joint.

[0102] Further, such as Figure 5 As shown, step S102 in the above embodiment, "constructing a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model based on the titanium crystal structure model obtained by cutting the titanium unit cell crystal plane according to the corresponding first cutting method", may specifically include the following steps:

[0103] S501, determine the first cutting method corresponding to the titanium crystal structure model, the second cutting method corresponding to the titanium-based solder crystal structure model, and the third cutting method corresponding to the high nitrogen steel crystal structure model, and cut the corresponding crystal structure models based on the different cutting methods to obtain multiple crystal structure models after cutting.

[0104] In the embodiment of the present application, the second cutting method is a method for cutting the titanium-based solder crystal structure model, and the third cutting method is a method for cutting the high-nitrogen steel crystal structure model. Three cutting methods corresponding to the titanium crystal structure model, the titanium-based solder crystal structure model and the high-nitrogen steel crystal structure model are determined, and the corresponding crystal structure models are cut according to different cutting methods to obtain the cut titanium crystal structure model, the titanium-based solder crystal structure model and the high-nitrogen steel crystal structure model. It should be noted that the cut titanium unit cell crystal structure model includes a plurality of titanium unit cell crystal planes; the cut titanium-based solder crystal structure model includes a plurality of titanium-based solder crystal planes; the cut high-nitrogen steel crystal structure model includes a plurality of high-nitrogen steel crystal planes; wherein each crystal plane includes a plurality of atomic layers.

[0105] Optionally, a preset crystal plane index (eg, 0 1 0) may be selected, and the corresponding crystal structure model may be segmented based on the crystal plane index and different segmentation methods.

[0106] S502, constructing a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model based on target titanium unit cell crystal planes that meet the crystal plane screening conditions among multiple titanium unit cell crystal planes, target titanium-based brazing filler metal crystal planes that meet the crystal plane screening conditions among multiple titanium-based brazing filler metal crystal planes, and target high nitrogen steel crystal planes that meet the crystal plane screening conditions among multiple high nitrogen steel crystal planes.

[0107] In the embodiment of the present application, the crystal plane screening condition is the condition for screening the target crystal plane, and the target titanium crystal cell crystal plane that meets the crystal plane screening condition is determined among the multiple titanium crystal cell crystal planes of the titanium crystal cell crystal structure model, the target titanium-based solder crystal plane that meets the crystal plane screening condition is determined among the multiple titanium-based solder crystal planes of the titanium-based solder crystal structure model, and the target high-nitrogen steel crystal plane that meets the crystal plane screening condition is determined among the multiple high-nitrogen steel crystal planes of the high-nitrogen steel crystal structure model, and based on the target titanium crystal cell crystal planes of the titanium crystal cell crystal structure model, the target titanium-based solder crystal planes of the titanium-based solder crystal structure model, and the target high-nitrogen steel crystal planes of the high-nitrogen steel crystal structure model, a titanium-titanium-based solder-high-nitrogen steel interface composite model is constructed, for example, Figure 3 The titanium / titanium-based brazing filler metal / high nitrogen steel interface model shown on the left.

[0108] It should be noted that when constructing the titanium-titanium-based solder-high nitrogen steel interface composite model, the titanium crystal structure model, the titanium-based solder crystal structure model and the high nitrogen steel crystal structure model can be adjusted based on the Redefine lattice (redefine crystal module) so that the titanium-first interface mismatch of the titanium crystal structure model, the titanium-based solder crystal structure model and the high nitrogen steel crystal structure model is less than a preset mismatch threshold (for example, 5%).

[0109] It should be noted that the present application does not impose too many restrictions on the specific method of constructing the titanium-titanium-based solder-high nitrogen steel interface composite model based on the target titanium unit cell crystal plane, the target titanium-based solder crystal plane and the target high nitrogen steel crystal plane, and can be set according to actual conditions.

[0110] As a possible implementation method, the atomic layers in multiple titanium unit cell crystal planes, multiple titanium-based solder crystal planes, and multiple high-nitrogen steel crystal planes are respectively subjected to convergence tests to obtain the convergence test results corresponding to each crystal plane; the target titanium unit cell crystal planes that meet the convergence requirements in multiple titanium unit cell crystal planes, the target titanium-based solder crystal planes that meet the convergence requirements in multiple titanium-based solder crystal planes, and the target high-nitrogen steel crystal planes that meet the convergence requirements in multiple high-nitrogen steel crystal planes are respectively screened out according to the convergence test results corresponding to each crystal plane; a titanium-titanium-based solder-high-nitrogen steel interface composite model is constructed based on the target titanium unit cell crystal planes, the target titanium-based solder crystal planes, and the target high-nitrogen steel crystal planes. Among them, the convergence test results are the results of the convergence test of the number of atomic layers in each crystal plane, for example, the convergence test of the number of atomic layers on the Z axis, and the crystal plane screening condition is the convergence requirement. For example, the Z-axis atomic layer number convergence test was performed on the atomic layers in multiple titanium unit cell crystal planes, multiple titanium-based solder crystal planes and multiple high-nitrogen steel crystal planes, and the results showed that 4 layers of Fe atoms, 5 layers of Ti atoms and 3 layers of titanium-based solder atoms converged to ensure that the energy of the crystal model was in a steady state. The corresponding three target crystal planes were the target titanium unit cell crystal planes, the target titanium-based solder crystal planes and the target high-nitrogen steel crystal planes. Based on these three target crystal planes, a titanium-titanium-based solder-high-nitrogen steel interface composite model was constructed.

[0111] Further, such as Figure 6 As shown, after constructing the titanium crystal structure model, the titanium-based brazing filler metal crystal structure model corresponding to the titanium-based brazing filler metal, and the high nitrogen steel crystal structure model, the method for predicting the high nitrogen steel / titanium interface bonding performance of the embodiment of the present application may further include the following steps:

[0112] S601, determining corresponding first optimization parameters based on titanium, titanium-based brazing filler metal and high nitrogen steel.

[0113] In the embodiment of the present application, the first optimization parameter is the parameter for structural optimization of the titanium crystal structure model, the titanium-based solder crystal structure model and the high-nitrogen steel crystal structure model. The corresponding first optimization parameter is determined according to titanium, titanium-based solder and high-nitrogen steel for subsequent processing. Among them, the first optimization parameter includes the k grid point for summing the Brillouin zone, the plane wave cutoff energy, the convergence standard of the system energy, the internal stress and the displacement; among them, the k grid point is 4×4×1 k grid point, the plane wave cutoff energy is 381eV, the convergence standard of the system energy is 1×10-5eV / atom, the internal stress is less than 0.05GPa, and the displacement is less than

[0114] S602, structurally optimizing the titanium crystal structure model, the titanium-based solder crystal structure model, and the high-nitrogen steel crystal structure model based on the first optimization parameter to obtain the titanium crystal structure model, the titanium-based solder crystal structure model, and the high-nitrogen steel crystal structure model after structural optimization.

[0115] In an embodiment of the present application, based on the first optimization parameters obtained according to titanium, titanium-based brazing filler metal and high nitrogen steel in step S601, the titanium crystal structure model, titanium-based brazing filler metal crystal structure model and high nitrogen steel crystal structure model constructed in the above embodiments are structurally optimized to obtain the structurally optimized titanium crystal structure model, titanium-based brazing filler metal crystal structure model and high nitrogen steel crystal structure model for subsequent processing.

[0116] Further, such as Figure 7 As shown, after constructing the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, the method for predicting the high nitrogen steel / titanium interface bonding performance of the embodiment of the present application may further include the following steps:

[0117] S701, obtaining corresponding second optimization parameters based on titanium, titanium-based brazing filler metal and high nitrogen steel.

[0118] In the embodiment of the present application, the second optimization parameter is the parameter for structural optimization of the titanium-titanium-based solder-high nitrogen steel interface composite model. The corresponding second optimization parameter is determined according to titanium, titanium-based solder and high nitrogen steel for subsequent processing. Among them, the second optimization parameter includes the k grid point for summing the Brillouin zone, the plane wave cutoff energy, the convergence standard of the system energy, the internal stress and the displacement; the k grid point is 3×3×1, the plane wave cutoff energy Ecut is 326.5eV, and the convergence standard of the system energy is 2×10 -5 eV / atom, internal stress less than 0.1GPa, displacement less than

[0119] S702, structurally optimizing the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model based on the second optimization parameter to obtain a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model after structural optimization.

[0120] In an embodiment of the present application, based on the second optimization parameters obtained according to titanium, titanium-based brazing filler metal and high nitrogen steel in step S701, the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model constructed in the above embodiment is structurally optimized to obtain a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model after structural optimization for subsequent processing.

[0121] Optionally, in addition, the thickness can be set in the Z direction perpendicular to the plane to vacuum layer to avoid interlayer interactions due to periodicity.

[0122] It should be noted that after constructing a variety of different titanium-titanium-based brazing filler metal-high nitrogen steel interface composite models, structural optimization calculations are also required, which will not be repeated here. Optionally, the structural optimization in this application can be completed by software, for example, CASTEP software package.

[0123] Further, such as Figure 8 As shown, step S104 in the above embodiment, "performing a multi-dimensional bonding performance evaluation on the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement to obtain a multi-dimensional bonding performance parameter index", may specifically include the following steps:

[0124] S801, calculating the interface adhesion work of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement based on a preset interface adhesion work calculation formula.

[0125] In the embodiment of the present application, the interface adhesion work calculation formula is a pre-set formula for calculating the interface adhesion work. Based on the interface adhesion work calculation formula, the interface adhesion work of different titanium-titanium-based brazing filler metal-high nitrogen steel interface composite models is calculated for subsequent processing.

[0126] Among them, the interfacial adhesion work is calculated by the following formula:

[0127] W ad =(E A +E B +E C -E A / B / C ) / 2A

[0128] Among them, W ad is the interfacial adhesion work; E A 、E B 、E C E is the total energy of the crystal structure model of the titanium metal surface, titanium-based brazing filler metal, and high nitrogen steel surface; A / B / C is the energy of the interface composite model; A is the cross-sectional area of ​​the interface composite model.

[0129] For example, according to the above-mentioned interface adhesion work calculation formula, the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic substitution can be calculated (for example, Figure 3 The first interface adhesion work of the titanium / titanium-based solder / high nitrogen steel interface composite model shown on the left is Wad=2.36937364J / m2, and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement (for example, Figure 3 The second interface adhesion work of the titanium / comparative brazing material 1 / high nitrogen steel interface composite model shown on the right is Wad=2.36937364 J / m2.

[0130] S802, based on the interface adhesion work of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement, obtain the corresponding bonding performance parameter index.

[0131] In the embodiment of the present application, based on the interface adhesion work of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement obtained in step S801, the corresponding bonding performance parameter indicators can be determined for subsequent processing.

[0132] Further, such as Fig. 9 As shown, step S104 in the above embodiment, "performing a multi-dimensional bonding performance evaluation on the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement to obtain a multi-dimensional bonding performance parameter index", can also specifically include the following steps:

[0133] S901, obtaining the first local electron function diagram, the first Mulliken layout analysis table and the first differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement, and the second local electron function diagram, the second Mulliken layout analysis table and the second differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement.

[0134] In the embodiment of the present application, the first local electron function diagram, the first Mulliken layout analysis table and the first differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement, and the second local electron function diagram, the second Mulliken layout analysis table and the second differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement are obtained for subsequent processing. For example, the first differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the second differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement corresponding to the comparison solder 1 are obtained here, as shown in FIG. Fig.10 As shown; obtain the first local electron function diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the second local electron function diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement corresponding to the comparison solder 1, as shown Fig.11As shown; the Mulliken layout analysis table of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the Mulliken layout analysis table of the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement corresponding to the comparative solder 1 are obtained, as shown in Table 1 below. Table 1 is the Mulliken layout analysis table of the main chemical bonds of the titanium / titanium-based solder / high nitrogen steel interface composite model (titanium-based solder before atomic replacement and comparative solder 1) before and after atomic replacement.

[0135] Table 1

[0136]

[0137] S902, based on the first localized electron function diagram, the first Mulliken layout analysis table, the first differential charge density diagram and the second localized electron function diagram, the second Mulliken layout analysis table and the second differential charge density diagram, obtain a multi-dimensional combination performance parameter index.

[0138] In an embodiment of the present application, based on the first local electron function diagram, the first Mulliken layout analysis table and the first differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement obtained in step S901, the second local electron function diagram, the second Mulliken layout analysis table and the second differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement, a multi-dimensional combination performance parameter index is obtained.

[0139] A further exemplary description of "determining a target titanium-titanium-based solder-high nitrogen steel interface composite model whose multi-dimensional combined performance parameter indicators meet the target requirements from the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement, and determining the titanium-based solder corresponding to the target titanium-titanium-based solder-high nitrogen steel interface composite model as the target titanium-based solder" is provided:

[0140] For example, the first interface adhesion work of the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model before atomic substitution is W ad =2.824033235J / m 2 , compared with the second interface adhesion work of the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement corresponding to solder 1, W ad =2.36937364J / m 2It can be seen that the first interface adhesion work is greater than the second interface adhesion work, indicating that the bonding performance of the titanium-titanium-based solder-high nitrogen steel interface is higher. At this time, the titanium-titanium-based solder-high nitrogen steel interface composite model with the largest interface adhesion work can be determined as the target titanium-titanium-based solder-high nitrogen steel interface composite model, that is, the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement. The titanium-based solder corresponding to the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement is determined as the target titanium-based solder.

[0141] For example, the binding performance can be evaluated by comparing the differential charge density maps, such as Fig.10 As shown, for Fig.10 In the titanium-titanium-based solder-high nitrogen steel interface composite model on the left, when the Fe atoms in the titanium-based solder lose charge, they also gain partial charge. The charge is mainly concentrated between the Ti atoms on the titanium surface and the Fe atoms in the solder, and between the Fe atoms in the high nitrogen steel and the Fe atoms in the solder, indicating that it is easy for Ti-Fe and Fe-Fe to form bonds. Fig.10 In the titanium-comparison solder 1-high nitrogen steel interface composite model on the right, the electron cloud near the Ti atom on the titanium surface moves toward the Fe atom in the solder, forming a Fe-Ti bond. The charge density near the Fe atom is higher than that of the Zr atom. Fe is electronegative to Zr. Moreover, there is a clear overlap of electron clouds between the Fe atom in the solder and the Fe atom on the surface of the high nitrogen steel, forming Fe-Fe. Fig.10 The charge density between the Fe atoms in the solder and the Ti atoms on the titanium surface in the left and right parts of the middle part shows that the charge density of the titanium / titanium-based solder / high nitrogen steel interface is stronger and the electron cloud overlap area is larger, so the strength of the Ti-Fe bond at the titanium / titanium-based solder / high nitrogen steel interface is greater than that of the Ti-Fe bond of the titanium / comparison solder 1 / high nitrogen steel, indicating that the titanium / titanium-based solder / high nitrogen steel interface bonding performance is better. At this time, the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement can be determined as the target titanium-titanium-based solder-high nitrogen steel interface composite model, and the titanium-based solder corresponding to the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement is determined as the target titanium-based solder.

[0142] For example, the characteristics of interatomic bonding can be quantitatively described by analyzing the electron localization function (ELF). At this time, the bonding performance can be evaluated by comparing the localized electron function diagram, such as Fig.11 As shown, for Fig.11In the titanium-titanium-based solder-high nitrogen steel interface composite model on the left, the ELF around the Fe(17) atom in the solder is evenly distributed, indicating that the electrons of the Fe atom are transferred to the nearest neighbor Ti atom in the solder. The bond between Fe(17) and Fe(14) is an ionic bond. At the same time, there are both ionic and covalent bonds between Fe(18) and Ti(25). Moreover, the Ti(7)-Ti(20) atoms are typical covalent bonds. The Fe(18) atom contributes electrons to Ti(25), and there is a weak covalent bond between Fe(18) and Ti(25). Fig.11 In the titanium-comparison brazing filler metal 1-high nitrogen steel interface composite model on the right, the Fe(19)-Ti(25) and Fe(6)-Ti(4) bonds have both ionic and covalent bond characteristics, while Fe(18)-Fe(14) tends to have ionic bond characteristics, while the covalent bond between Ti(25) and Ti(5) plays a dominant role. Fig.11 From the local electron function diagrams in the left and right parts, it can be concluded that the average ELF between different atoms at the titanium / titanium-based solder / high nitrogen steel interface is larger than that at the titanium / comparison solder 1 / high nitrogen steel interface, and the main chemical bonds are mostly covalent bonds, indicating that the probability of electron pairs appearing in the titanium / titanium-based solder / high nitrogen steel interface is higher, the probability of bonding is higher, and the interface has better bonding performance. At this time, the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement can be determined as the target titanium-titanium-based solder-high nitrogen steel interface composite model, and the titanium-based solder corresponding to the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement is determined as the target titanium-based solder.

[0143] For example, comparing the Mulliken bond layout can reflect the distribution of electrons at the interface and quantify the type and strength of the bonding action. At this time, the bonding performance can be evaluated by comparing the Mulliken layout analysis table. As shown in Table 1 above, the Fe(18)-Ti(25) bond at the titanium / titanium-based solder / high nitrogen steel interface has both ionic and covalent bond properties, with a bond length of 0.185518, while the Fe(19)-Ti(25) at the titanium / titanium-based solder / high nitrogen steel interface exhibits ionic bond properties, and the bond length is greater than 0.185518. At the same time, the Ti(5)-Ti(15) bond length is greater than that of Ti(20)-Ti(7), indicating that the Ti(20)-Ti(7) bond is stronger. Therefore, the bonding strength of the titanium / titanium-based solder / high nitrogen steel interface is higher than that of the titanium / comparison solder 1 / high nitrogen steel interface. At this time, the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement can be determined as the target titanium-titanium-based solder-high nitrogen steel interface composite model, and the titanium-based solder corresponding to the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement can be determined as the target titanium-based solder.

[0144] By comparing the bonding performance parameter indicators of titanium / titanium-based brazing filler metal / high nitrogen steel interface and titanium / comparison brazing filler metal 1 / high nitrogen steel interface, it is finally determined that the bonding performance of the titanium / titanium-based brazing filler metal / high nitrogen steel interface is the best, thereby determining the target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model and the corresponding target titanium-based brazing filler metal.

[0145] It should be noted that the bonding performance evaluation of the titanium / comparison solder 2 / high nitrogen steel interface composite model corresponding to comparison solder 2 in this application is the same as the description of the above-mentioned comparison solder 1, and will not be repeated here.

[0146] Fig.12 is a schematic diagram of the structure of a device for predicting high nitrogen steel / titanium interface bonding performance according to an embodiment of the present application, such as Fig.12 As shown, the device 1200 for predicting high nitrogen steel / titanium interface bonding performance according to the embodiment of the present application may specifically include:

[0147] The first construction module 1201 is used to construct a titanium crystal structure model, a titanium-based solder crystal structure model corresponding to the titanium-based solder, and a high-nitrogen steel crystal structure model; wherein the Ti atoms, Fe atoms, and Zr atoms in the titanium-based solder crystal structure model correspond to the Ti element, Fe element, and Zr element in the titanium-based solder; and the proportions of the Ti element, Fe element, and Zr element in titanium-based solders of different components are different.

[0148] The second construction module 1202 is used to construct a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model based on the titanium unit cell crystal plane obtained by cutting the titanium crystal structure model according to the corresponding first cutting method.

[0149] The replacement module 1203 is used to obtain a plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement by performing atomic replacement on the atoms of the titanium-titanium-based solder-high nitrogen steel interface composite model multiple times; wherein the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement correspond to titanium-based solders of different components, respectively.

[0150] The evaluation module 1204 is used to perform multi-dimensional bonding performance evaluation on the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement to obtain multi-dimensional bonding performance parameter indicators.

[0151] Determination module 1205 is used to determine a target titanium-titanium-based solder-high nitrogen steel interface composite model whose multi-dimensional combined performance parameter indicators meet the target requirements from the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement, and determine the titanium-based solder corresponding to the target titanium-titanium-based solder-high nitrogen steel interface composite model as the target titanium-based solder.

[0152] In a possible implementation manner, the second building module is specifically configured to:

[0153] Determine a first cutting method corresponding to a titanium crystal structure model, a second cutting method corresponding to a titanium-based solder crystal structure model, and a third cutting method corresponding to a high-nitrogen steel crystal structure model, and cut the corresponding crystal structure models based on different cutting methods to obtain a plurality of crystal structure models after cutting; wherein the titanium unit cell crystal structure model after cutting includes a plurality of titanium unit cell crystal planes; the titanium-based solder crystal structure model after cutting includes a plurality of titanium-based solder crystal planes; the high-nitrogen steel crystal structure model after cutting includes a plurality of high-nitrogen steel crystal planes;

[0154] A titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model is constructed based on target titanium unit cell crystal planes among multiple titanium unit cell crystal planes that meet the crystal plane screening conditions, target titanium-based brazing filler metal crystal planes among multiple titanium-based brazing filler metal crystal planes that meet the crystal plane screening conditions, and target high nitrogen steel crystal planes among multiple high nitrogen steel crystal planes that meet the crystal plane screening conditions.

[0155] In a possible implementation manner, each crystal plane includes a plurality of atomic layers; the second building block is specifically configured to:

[0156] Convergence tests are performed on the atomic layers in multiple titanium unit cell crystal planes, multiple titanium-based brazing filler metal crystal planes, and multiple high-nitrogen steel crystal planes, respectively, to obtain the convergence test results corresponding to each crystal plane;

[0157] According to the convergence test results corresponding to each crystal plane, a target titanium unit cell crystal plane that meets the convergence requirements among multiple titanium unit cell crystal planes, a target titanium-based solder crystal plane that meets the convergence requirements among multiple titanium-based solder crystal planes, and a target high-nitrogen steel crystal plane that meets the convergence requirements among multiple high-nitrogen steel crystal planes are screened out respectively;

[0158] A titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model was constructed based on the target titanium unit cell crystal plane, target titanium-based brazing filler metal crystal plane and target high nitrogen steel crystal plane.

[0159] In a possible implementation, the device for predicting high nitrogen steel / titanium interface bonding performance further includes:

[0160] The first determination module 1201 is used to determine the corresponding first optimization parameters based on titanium, titanium-based solder and high nitrogen steel after constructing the titanium crystal structure model, the titanium-based solder crystal structure model corresponding to the titanium-based solder and the high nitrogen steel crystal structure model; wherein the first optimization parameters include the k grid points for summing the Brillouin zones, the plane wave cutoff energy, the convergence standard of the system energy, the internal stress and the displacement; wherein the k grid points are 4×4×1 k grid points, the plane wave cutoff energy is 381eV, the convergence standard of the system energy is 1×10-5eV / atom, the internal stress is less than 0.05GPa, and the displacement is less than

[0161] The first optimization module is used to optimize the titanium crystal structure model, the titanium-based solder crystal structure model and the high-nitrogen steel crystal structure model based on the first optimization parameter to obtain the titanium crystal structure model, the titanium-based solder crystal structure model and the high-nitrogen steel crystal structure model after structural optimization.

[0162] In a possible implementation, the device for predicting high nitrogen steel / titanium interface bonding performance further includes:

[0163] The second determination module is used to obtain the corresponding second optimization parameters based on titanium, titanium-based solder and high nitrogen steel after constructing the titanium-titanium-based solder-high nitrogen steel interface composite model; wherein the second optimization parameters include k grid points for summing the Brillouin zone, plane wave cutoff energy, convergence standard of system energy, internal stress and displacement; k grid points are 3×3×1, plane wave cutoff energy Ecut is 326.5eV, and the convergence standard of system energy is 2×10 -5 eV / atom, internal stress less than 0.1GPa, displacement less than

[0164] The second optimization module is used to perform structural optimization on the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model based on the second optimization parameters to obtain a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model after structural optimization.

[0165] In a possible implementation, the multi-dimensional bonding performance parameter index includes interface adhesion work, differential charge density map, electron localization function map, Mulliken layout analysis table, and the evaluation module is specifically used for:

[0166] The interface adhesion work of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the interface adhesion work of the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement are calculated based on the preset interface adhesion work calculation formula;

[0167] Based on the interface adhesion work of the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model after atomic replacement, the corresponding bonding performance parameter indicators are obtained.

[0168] In a possible implementation, the interfacial adhesion work is calculated by the following formula:

[0169] W ad =(E A +E B +E C -E A / B / C ) / 2A

[0170] Among them, W adis the interfacial adhesion work; E A 、E B 、E C E is the total energy of the crystal structure model of the titanium metal surface, titanium-based brazing filler metal, and high nitrogen steel surface; A / B / C is the energy of the interface composite model; A is the cross-sectional area of ​​the interface composite model.

[0171] In a possible implementation, the evaluation module is further specifically used for:

[0172] Obtaining a first local electron function diagram, a first Mulliken layout analysis table, and a first differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement, and a second local electron function diagram, a second Mulliken layout analysis table, and a second differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement;

[0173] Based on the first localized electron function diagram, the first Mulliken layout analysis table, the first differential charge density diagram and the second localized electron function diagram, the second Mulliken layout analysis table and the second differential charge density diagram, multi-dimensional combined performance parameter indicators are obtained.

[0174] The device for predicting the high nitrogen steel / titanium interface bonding performance provided in the embodiment of the present application constructs a titanium crystal structure model, a titanium-based solder crystal structure model corresponding to the titanium-based solder, and a high nitrogen steel crystal structure model, and constructs a titanium-titanium-based solder-high nitrogen steel interface composite model based on the titanium crystal structure model. The atoms of the titanium-titanium-based solder-high nitrogen steel interface composite model are atomically replaced multiple times to obtain a plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement, and the titanium-titanium-based solder-high nitrogen steel interface composite models before atomic replacement are calculated. The titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement are used for multi-dimensional bonding performance evaluation to obtain multi-dimensional bonding performance parameter indicators, and the target titanium-titanium-based solder-high nitrogen steel interface composite model whose multi-dimensional bonding performance parameter indicators meet the target requirements is determined from the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement, and the titanium-based solder corresponding to the target titanium-titanium-based solder-high nitrogen steel interface composite model is determined as the target titanium-based solder. The device for predicting the high nitrogen steel / titanium interface bonding performance of the present application constructs a titanium crystal structure model, a titanium-based brazing filler metal crystal structure model and a high nitrogen steel crystal structure model to construct a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, performs atomic replacement on the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model multiple times to obtain multiple different titanium-titanium-based brazing filler metal-high nitrogen steel interface composite models after atomic replacement, performs multi-dimensional bonding performance evaluation on the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite models before and after atomic replacement, determines a target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, and determines the titanium-based brazing filler metal corresponding to the target titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model as the target titanium-based brazing filler metal, can predict the influence of different titanium-based brazing fillers on the bonding performance of the titanium / high nitrogen steel interface, so as to determine the target titanium-based brazing filler metal with the best bonding performance, and use of the target titanium-based brazing filler metal can ensure the performance of the titanium / high nitrogen steel brazing joint, thereby improving the production efficiency of the titanium / high nitrogen steel brazing joint.

[0175] like Fig.13 As shown, an electronic device 1300 provided in an embodiment of the present application includes: a processor 1301, a memory 1302 and a bus, wherein the memory 1302 stores machine-readable instructions executable by the processor 1301. When the electronic device is running, the processor 1301 communicates with the memory 1302 through the bus, and the processor 1301 executes the machine-readable instructions to perform the steps of the method for predicting the high nitrogen steel / titanium interface bonding performance as described above.

[0176] Specifically, the above-mentioned memory 1302 and processor 1301 can be general-purpose memory and processor, which are not specifically limited here. When the processor 1301 runs the computer program stored in the memory 1302, the above-mentioned method for predicting the high nitrogen steel / titanium interface bonding performance can be executed.

[0177] Those skilled in the art can clearly understand that, for the convenience and simplicity of description, the specific working process of the system and device described above can refer to the corresponding process in the method embodiment, and will not be repeated in this application. In the several embodiments provided in this application, it should be understood that the disclosed system, device and method can be implemented in other ways. The device embodiments described above are merely schematic. For example, the division of the modules is only a logical function division. There may be other division methods in actual implementation. For example, multiple modules or components can be combined or integrated into another system, or some features can be ignored or not executed. Another point is that the mutual coupling or direct coupling or communication connection shown or discussed can be through some communication interfaces, indirect coupling or communication connection of devices or modules, which can be electrical, mechanical or other forms.

[0178] The modules described as separate components may or may not be physically separated, and the components shown as modules may or may not be physical units, that is, they may be located in one place or distributed on multiple network units. Some or all of the units may be selected according to actual needs to achieve the purpose of the solution of this embodiment.

[0179] In addition, each functional unit in each embodiment of the present application may be integrated into one processing unit, or each unit may exist physically separately, or two or more units may be integrated into one unit.

[0180] If the functions are implemented in the form of software functional units and sold or used as independent products, they can be stored in a non-volatile computer-readable storage medium that is executable by a processor. Based on this understanding, the technical solution of the present application, or the part that contributes to the prior art or the part of the technical solution, can be embodied in the form of a software product, which is stored in a storage medium and includes several instructions for a computer device (which can be a personal computer, server, or network device, etc.) to perform all or part of the steps of the deployment method described in each embodiment of the present application. The aforementioned storage medium includes: various media that can store program codes, such as USB flash drives, mobile hard drives, ROM, RAM, magnetic disks, or optical disks.

[0181] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for predicting high nitrogen steel / titanium interface bonding performance, characterized in that: The method comprises: Constructing a titanium crystal structure model, a titanium-based solder crystal structure model corresponding to the titanium-based solder, and a high-nitrogen steel crystal structure model; wherein the Ti atoms, Fe atoms, and Zr atoms in the titanium-based solder crystal structure model correspond to the Ti element, Fe element, and Zr element in the titanium-based solder; and the proportions of the Ti element, Fe element, and Zr element in titanium-based solders of different components are different; Based on the titanium crystal structure model obtained by cutting the titanium unit cell crystal plane according to the corresponding first cutting method, a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model is constructed; By repeatedly performing atomic replacement on the atoms of the titanium-titanium-based solder-high nitrogen steel interface composite model, a plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after the atomic replacement are obtained; wherein the titanium-titanium-based solder-high nitrogen steel interface composite model before the atomic replacement and the plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after the atomic replacement correspond to titanium-based solders of different components, respectively; The multi-dimensional bonding performance evaluation was conducted on the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement to obtain multi-dimensional bonding performance parameter indicators; From the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement, determine the target titanium-titanium-based solder-high nitrogen steel interface composite model whose multi-dimensional combined performance parameter indicators meet the target requirements, and determine the titanium-based solder corresponding to the target titanium-titanium-based solder-high nitrogen steel interface composite model as the target titanium-based solder.

2. The method according to claim 1, characterized in that The titanium unit cell crystal plane obtained by cutting the titanium crystal structure model according to the corresponding first cutting method is used to construct a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, including: Determine a first cutting method corresponding to the titanium crystal structure model, a second cutting method corresponding to the titanium-based solder crystal structure model, and a third cutting method corresponding to the high-nitrogen steel crystal structure model, and cut the corresponding crystal structure models based on different cutting methods to obtain a plurality of crystal structure models after cutting; wherein the titanium unit cell crystal structure model after cutting includes a plurality of titanium unit cell crystal planes; the titanium-based solder crystal structure model after cutting includes a plurality of titanium-based solder crystal planes; the high-nitrogen steel crystal structure model after cutting includes a plurality of high-nitrogen steel crystal planes; The titanium-titanium-based brazing filler material-high nitrogen steel interface composite model is constructed based on target titanium unit cell crystal planes that meet the crystal plane screening conditions among multiple titanium unit cell crystal planes, target titanium-based brazing filler material crystal planes that meet the crystal plane screening conditions among multiple titanium-based brazing filler material crystal planes, and target high nitrogen steel crystal planes that meet the crystal plane screening conditions among multiple high nitrogen steel crystal planes.

3. The method according to claim 2, characterized in that Each crystal plane includes a plurality of atomic layers; the titanium-titanium-based solder-high nitrogen steel interface composite model is constructed based on a target titanium unit cell crystal plane that meets the crystal plane screening conditions among a plurality of titanium unit cell crystal planes, a target titanium-based solder crystal plane that meets the crystal plane screening conditions among a plurality of titanium-based solder crystal planes, and a target high nitrogen steel crystal plane that meets the crystal plane screening conditions among a plurality of high nitrogen steel crystal planes, including: Conducting convergence tests on the atomic layers in the plurality of titanium unit cell crystal planes, the plurality of titanium-based brazing filler metal crystal planes, and the plurality of high nitrogen steel crystal planes, respectively, to obtain convergence test results corresponding to each crystal plane; According to the convergence test results corresponding to each crystal plane, a target titanium unit cell crystal plane that meets the convergence requirements among multiple titanium unit cell crystal planes, a target titanium-based solder crystal plane that meets the convergence requirements among multiple titanium-based solder crystal planes, and a target high-nitrogen steel crystal plane that meets the convergence requirements among multiple high-nitrogen steel crystal planes are respectively screened out; The titanium-titanium-based solder-high nitrogen steel interface composite model is constructed based on the target titanium unit cell crystal plane, the target titanium-based solder crystal plane and the target high nitrogen steel crystal plane.

4. The method according to claim 1, characterized in that: After constructing the titanium crystal structure model, the titanium-based brazing filler metal crystal structure model corresponding to the titanium-based brazing filler metal, and the high-nitrogen steel crystal structure model, the method further includes: The corresponding first optimization parameters are determined based on the titanium, the titanium-based brazing filler metal and the high nitrogen steel; wherein the first optimization parameters include the k grid points for summing the Brillouin zones, the plane wave cutoff energy, the convergence standard of the system energy, the internal stress and the displacement; wherein the k grid points are 4×4×1 k grid points, the plane wave cutoff energy is 381eV, the convergence standard of the system energy is 1×10-5eV / atom, the internal stress is less than 0.05GPa, and the displacement is less than Based on the first optimization parameter, the titanium crystal structure model, the titanium-based brazing filler metal crystal structure model and the high nitrogen steel crystal structure model are structurally optimized to obtain the titanium crystal structure model, the titanium-based brazing filler metal crystal structure model and the high nitrogen steel crystal structure model after structural optimization.

5. The method according to claim 1, characterized in that After constructing the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model, the method further comprises: The corresponding second optimization parameters are obtained based on the titanium, the titanium-based brazing filler metal and the high nitrogen steel; wherein the second optimization parameters include the k grid points for summing the Brillouin zone, the plane wave cutoff energy, the convergence standard of the system energy, the internal stress and the displacement; the k grid points are 3×3×1, the plane wave cutoff energy Ecut is 326.5 eV, and the convergence standard of the system energy is 2×10 -5 eV / atom, the internal stress is less than 0.1GPa, and the displacement is less than The titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model is structurally optimized based on the second optimization parameter to obtain the titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model after structural optimization.

6. The method according to claim 1, characterized in that The multi-dimensional bonding performance parameter index includes interface adhesion work, differential charge density diagram, electron localization function diagram, Mulliken layout analysis table, and the multi-dimensional bonding performance evaluation is performed on the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement to obtain multi-dimensional bonding performance parameter index, including: Calculating the interface adhesion work of the titanium-titanium-based solder-high nitrogen steel interface composite model before the atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after the atomic replacement based on a preset interface adhesion work calculation formula; Based on the interface adhesion work of the titanium-titanium-based solder-high nitrogen steel interface composite model before the atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after the atomic replacement, the corresponding bonding performance parameter index is obtained.

7. The method according to claim 6, characterized in that The interfacial adhesion work is calculated by the following formula: W ad =(E A +E B +E C -HAVE BEEN A / B / C ) / 2A Among them, W ad is the interfacial adhesion work; E A 、E B 、E C E is the total energy of the crystal structure model of the titanium metal surface, titanium-based brazing filler metal, and high nitrogen steel surface; A / B / C is the energy of the interface composite model; A is the cross-sectional area of ​​the interface composite model.

8. The method according to claim 6, characterized in that The multi-dimensional bonding performance evaluation of the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement is performed to obtain multi-dimensional bonding performance parameter indicators, and also includes: Obtaining a first local electron function diagram, a first Mulliken layout analysis table, and a first differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model before the atomic replacement, and a second local electron function diagram, a second Mulliken layout analysis table, and a second differential charge density diagram of the titanium-titanium-based solder-high nitrogen steel interface composite model after the atomic replacement; Based on the first localized electron function diagram, the first Mulliken layout analysis table, the first differential charge density diagram and the second localized electron function diagram, the second Mulliken layout analysis table and the second differential charge density diagram, a multi-dimensional combination performance parameter index is obtained.

9. A device for predicting high nitrogen steel / titanium interface bonding properties, characterized in that: The device comprises: The first construction module is used to construct a titanium crystal structure model, a titanium-based solder crystal structure model corresponding to the titanium-based solder, and a high-nitrogen steel crystal structure model; wherein the Ti atoms, Fe atoms, and Zr atoms in the titanium-based solder crystal structure model correspond to the Ti element, Fe element, and Zr element in the titanium-based solder; and the proportions of the Ti element, Fe element, and Zr element in titanium-based solders of different components are different; A second construction module is used to construct a titanium-titanium-based brazing filler metal-high nitrogen steel interface composite model based on the titanium unit cell crystal plane obtained by cutting the titanium crystal structure model according to the corresponding first cutting method; A replacement module is used to obtain a plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement by performing atomic replacement on the atoms of the titanium-titanium-based solder-high nitrogen steel interface composite model for multiple times; wherein the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the plurality of different titanium-titanium-based solder-high nitrogen steel interface composite models after atomic replacement correspond to titanium-based solders of different components, respectively; An evaluation module is used to perform multi-dimensional bonding performance evaluation on the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement to obtain multi-dimensional bonding performance parameter indicators; A determination module is used to determine a target titanium-titanium-based solder-high nitrogen steel interface composite model whose multi-dimensional combined performance parameter indicators meet the target requirements from the titanium-titanium-based solder-high nitrogen steel interface composite model before atomic replacement and the titanium-titanium-based solder-high nitrogen steel interface composite model after atomic replacement, and determine the titanium-based solder corresponding to the target titanium-titanium-based solder-high nitrogen steel interface composite model as the target titanium-based solder.

10. An electronic device, characterized in that: include: A processor, a memory and a bus, wherein the memory stores machine-readable instructions executable by the processor, and when the electronic device is running, the processor and the memory communicate via the bus, and when the machine-readable instructions are executed by the processor, the steps of the method for predicting the high nitrogen steel / titanium interface bonding performance as described in any one of claims 1 to 8 are performed.

Citation Information

Patent Citations

  • Method for forecasting room-temperature mechanical property of TC4 alloy forge piece

    CN105631160A

  • Method for establishing pyrolytic carbon PyC interface model of ceramic-based composite material and predicting shear strength

    CN112668204A

  • Method for improving performance of dissimilar metal melt-brazed joint through carbon nanotubes

    CN112894047A

  • Method for predicting nitride of non-magnetic steel connection interface

    CN114749744A

  • System for evaluating soldered joint section

    JP2006313127A

Cited By

  • Method and device for regulating and controlling performance of connection interface of nickel-copper brazing filler metal and diamond

    CN119541740A

  • Method and device for regulating and controlling performance of high-nitrogen steel / nickel-copper brazing filler metal through active elements

    CN119560080A

  • High-throughput calculation method for predicting performance of tungsten-molybdenum alloy connection interface

    CN119626417A